2019
DOI: 10.1103/physrevd.100.063516
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic gravitational-wave background from axion-monodromy oscillons in string theory during preheating

Abstract: Axion monodromy is a generic phenomenon in string compactifications. We investigate the production of gravitational-wave background from axion monodromy inflation during preheating. By performing lattice simulations using pseudospectral methods, we find that significant single-peak stochastic gravitational-wave backgrounds are generated during preheating for asymptotic linear |φ| and φ 2/3 potentials in axion monodromy inflation and cuspy potentials. This may allow us to explore string compactifications throug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Oscillon production Oscillons are long-lived compact objects (Gleiser 1994) that can be formed in the early Universe in a variety of post-inflationary scenarios which involve a preheating-like phase (Amin and Shirokoff 2010;Amin et al , 2012Zhou et al 2013;Amin 2013;Lozanov and Amin 2014;Antusch et al 2017Antusch et al , 2018aLozanov and Amin 2018;Amin et al 2018;Antusch et al 2019;Sang and Huang 2019;Lozanov and Amin 2019;Fodor 2019;Hiramatsu et al 2021). Their dynamics is a possible source of GW production.…”
Section: (P)reheatingmentioning
confidence: 99%
“…Oscillon production Oscillons are long-lived compact objects (Gleiser 1994) that can be formed in the early Universe in a variety of post-inflationary scenarios which involve a preheating-like phase (Amin and Shirokoff 2010;Amin et al , 2012Zhou et al 2013;Amin 2013;Lozanov and Amin 2014;Antusch et al 2017Antusch et al , 2018aLozanov and Amin 2018;Amin et al 2018;Antusch et al 2019;Sang and Huang 2019;Lozanov and Amin 2019;Fodor 2019;Hiramatsu et al 2021). Their dynamics is a possible source of GW production.…”
Section: (P)reheatingmentioning
confidence: 99%
“…Nucleosynthesis also provides strong constraints on the QCD axion, even in the absence of a primordial magnetic field [148]. The interplay between solitons and electromagnetic fields can affect the rate of energy transfer and equation of state during reheating, as well as gravitational wave production, and spectral distortions during the early universe [90,126,127,[149][150][151][152][153][154].…”
Section: Early Universementioning
confidence: 99%
“…A lot of studies on gravitational waves emitted during the formation of oscillons can be found in the recent literature [29][30][31][32][33][34][35][36][37][38]. In this paper, we try to address the following question: How much do the properties of gravitational waves emitted from the formation of oscillons, such as the shape and the amplitude of the power spectrum, depend on the potential of a source scalar field.…”
Section: Jhep03(2021)021mentioning
confidence: 99%